Mobile ad-hoc networks: MANET - Mikarić Bratislav; Spalević Petar; Jakšić Branimir (Trendovi u Poslovanju)
Currently in 2018, 7.6 billion people are in the world, and 8.6 billion mobile devices. As mobile phones have completely changed the meaning of the term to be available, a similar change in the wait and laptops users is, so it is only a matter of time before the new way to use your notebooks will change your habits and make life easier. As modern man is becoming increasingly accustomed to the availability of the 'network' (the Internet), where he can find almost every necessary information, he is increasingly integrating in his life, for example, if one wants to quickly find out where one can buy a book of a particular author, or on a specific topic, which pharmacies are open, how to find the street etc. Today, wireless internet access at airports, restaurants, hotels is almost everywhere , and such approaches are based on previously installed infrastructure such as wireless access point (wireless access point) through which you connect your device to the Internet or communicate with another person and exchange data. This way of accessing the Internet while on the go-via a laptop computer would require an infrastructure like the GSM network. That is why we started to develop a different network model, which are ad-hoc networks, that is, Mobile Ad-hoc Networks, as an ad-hoc network.